2008
DOI: 10.4161/psb.6185
|View full text |Cite
|
Sign up to set email alerts
|

Role of HY5 in abscisic acid response in seeds and seedlings

Abstract: response in late embryogenesis-abundant (LEA) gene expression, seed germination, seedling establishment and root growth; (2) HY5 mediates these ABA responses partly by regulating the transcription of the seed/seedling-specific ABA signaling regulator ABI5, (3) ABA specifically enhances HY5 binding to the ABI5 chromatin and; (4) ABI5 sensitizes light repression of hypocotyl elongation. These results raise interesting questions on the interaction of light signaling and ABA signaling and its potential significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…1C and 2), we investigated the role of HY5 in seed responses to karrikins. Although hy5-1 seed exhibited reduced dormancy, consistent with a recent report (44), its germination was significantly responsive to karrikins ( Fig. S4 A and B).…”
Section: Kar 1 Enhances Arabidopsis Seed Germination Under Low Light supporting
confidence: 79%
“…1C and 2), we investigated the role of HY5 in seed responses to karrikins. Although hy5-1 seed exhibited reduced dormancy, consistent with a recent report (44), its germination was significantly responsive to karrikins ( Fig. S4 A and B).…”
Section: Kar 1 Enhances Arabidopsis Seed Germination Under Low Light supporting
confidence: 79%
“…10,[17][18][19][20] Previously, we reported that HY5, a well-characterized component in the light signal transduction pathway, also mediates ABA response during seed germination and lateral root development. 21,22 Using the enhanced light response as a phenotype, we conducted a genetic screen and isolated fry1 suppressors with reduced light sensitivity. 20 Map-based cloning of several of these suppressors identified that phyB and hy1 mutant alleles were among the suppressors of fry1 light sensitivity.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…In fact, besides Arabidopsis, the overexpression transgenics of the full-length AtHY5 orthologs in the same organism have not been raised, and that makes it difficult for us to conclude whether full-length HY5 overexpression causes semidwarfism only in rice (this study) or in other organisms too. AtHY5 is known to be involved in auxin, GA, cytokinin, ABA, ethylene, and strigolactone signaling; while it represses ethylene, GA, and auxin signaling, it promotes ABA signaling (Cluis et al, 2004;Vandenbussche et al, 2007;Alabadí et al, 2008;Chen and Xiong, 2008;Li et al, 2011b;Yu et al, 2013). In this study too, the expression of genes associated with the biosynthesis of GA, jasmonic acid, ethylene, and brassinosteroid as well as cytokinin glucosylation was altered in OsbZIP48 OE transgenics.…”
Section: Osbzip48 Controls Plant Height In Ricementioning
confidence: 62%